Effect of pre-sowing irrigation and soil mulch on yield attributes, yield and wateruse of chickpea (Cicer arietinum), linseed (Linum usitatissimum) and Indian mustard (Brassica juncea) - PRASAD, S N; SINGH, RATAN; RAO, D H (The Indian Journal of Agricultural Sciences, 2013)
A field experiment was conducted during the winter season of 1990-91 to 1992-93 to study the effect of 3 depths of pre-sowing irrigation (0,5 and 10 cm) and soil mulch on yield attributes, yield, water-use and water-use efficiency of chickpea (Cicer arietinum L.), linseed (Linum usitatissimum L.) and Indian mustard (Brassica juncea (L.) Czemj. & Cosson.). Data revealed that yield attributes, grain and chickpea equivalent yield and"water use of crops progressively increased with the depth of irrigation. The average increase in grain yield was 50, 61 and 80%, and 63, 69 and 92% in chickpea, linseed and indian mustard respectively with 5 and 10 cm irrigation. However, the yield differences between 5 Dnd 10 cm irrigation were significantly at par. Indian mustard gave the highest chickpea equivalent yield (2 094 kg/ ha) which was 29.7 and 76.6% higher than chickpea and linseed respectively. The water-use of chickpea (125 mm) and Indian mustard (124 mm) was 8.7 and 7.8% higher respectively than that of linseed. Irrigation also increased the water-use efficiency. Indian mustard showed the highest water-use efficiency (16.5 kg/ha-mm) and linseed the lowest (10.2 kg/ha-mm). Soil mulch alone or in combination with irrigation was not found effective.